My small world in biomedical research - Othman, Fauziah (Universiti Putra Malaysia Press, 2011)
Biomedical research in general simply known as medical research, is the basic research, applied research, or translational researchconducted to aid and support the body of knowledge in the field of medicine. Cancer is a leading cause of death worldwide representing 13% of all deaths (over 11 million in 2030), breast cancer is the most common diagnosed type of cancer among women accounting for about 28% of all female cancer cases, while liver cancer is the third most common cause of death from cancer worldwide. Workers exposed to formaldehyde vapour have been well documented to have an association between formaldehyde exposure and several cancers, including nasopharyngeal cancer and leukemia. A study was conducted in hatching chicks which represented a working environment that was exposed to the 10.9 ppm formaldehyde vapour, the result illustrated that there were pathological changes in the respiratory epithelium. And there was also pre-cancerous lesion seen in the epithelium where the normal psuedostratified columnar ciliated epithelium was replaced by stratified squamous epithelium in the trachea. The existing treatment for cancer such as surgery, chemotherapy and radiotherapy are not always effective and can cause significant side effects. Thus, the author ventured into cancer research via two approaches:In viro therapy, where, Newcastle Disease Virus was used whilst, in herbal therapy where Azadirachta Indica A.Juss (Neem) Extracts, Cola Nut (Cola Nitida) Fruit Aqueous Extract and Strobilanthes Crispus Extract were used in in-vitro and in-vivo study. The oncolytic effect of Newcastle Disease Virus (NDV) strain AF2240 was investigated on the MCF-7, MDA-MB-231 breast cancer cell lines and 3T3 fibroblast. There were destruction of the cytoskeletal protein, structural and ultrastructural changes, as well as molecular changes of the oncogenes which enlightened the important biological discoveries of apoptosis in the cancer cells, however, not in the normal cells.The oncolytic effect of Newcastle Disease Virus AF2240 on Allografted 4T1 Breast Cancer Cells In Balb/c mice was well demonstrated and NDV-AF2240 was detected via In situ reverse transcriptase polymerase chain reaction (in situ RT-PCR), polyclonal chicken antibody and goat anti-chicken antibody conjugated with fluorescein isothiocynate (FITC) using confocal laser scanning microscopy (CLSM) and negative staining transmission electron microscopy (NSTEM). The pre-clinical study of this virus is proven to be safe and effective in animal study, however, further study is needed to understand the underlying mechanism in making the NDV strain of AF2240 as an anti-cancer agent in human.In herbal theraphy research, Berberis Vulgaris(L.) Fruit Extract, Azadirachta Indica A.Juss (Neem) Extracts, Strobilanthes Crispus Extract, and Cola Nut (Cola Nitida) Fruit Aqueous Extract, were found to contain high antioxidant and prevent the formation or viability of cancer cells. In vitro and in-vivo study showed that they have great potential to be developed either into functional food or further develop into drugs which can be used to either treat liver, breast and cervical cancers. Tissue and organ failure, resulting from various forms of injury such as traumatic, metabolic, inflammatory and other diseases normally lead to lost of tissue, organ and system function. To overcome these problems, researchers try to implement tissue engineering as a new approach and to assure the proper re-establishment of organ function, the structural and ultrastructural changes and expression of protein markers during re-modelling of tissue-engineered skin, tissue engineered cornea and tissue engineered bone. In orthopaedics, administration of antibiotics does not provide good local bone response due to poor vascularisation of bone tissue; low drug penetration and recurrent cases are high due to formation and presence of biofilm. The author again takes the lead to develop a biocompatible material in-cooperated with antibiotic to overcome the problem mentioned above. As cancer, tissue and organ lost can either be life threatening or compensating quality of life, biomedical research play an important role to support the medical scenario towards human health and wealth creation to the nation.